ANGKA KECELAKAAN KERJA NAIK PENINGKATAN DALAM 8 TAHUN TERAKHIR : PENGIMPLEMENTASIAN PROGRAM ZERO ACCIDENT AWARD - Agris Bagus Puta Pratama; Galang Satrio Nugroho; Mardian Putra Frans (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2024)
This research discusses important aspects in achieving complete mobility in a company, with a focus on labor aspects and Occupational Health and Safety (K3). Even though the company received the